2014
DOI: 10.18632/oncotarget.1895
|View full text |Cite
|
Sign up to set email alerts
|

A long non-coding RNA signature to improve prognosis prediction of colorectal cancer

Abstract: Increasing evidence suggests long non-coding RNAs (lncRNAs) are frequently aberrantly expressed in cancers, however, few related lncRNA signatures have been established for prediction of cancer prognosis. We aimed to develop a lncRNA signature to improve prognosis prediction of colorectal cancer (CRC). Using a lncRNA-mining approach, we performed lncRNA expression profiling in large CRC cohorts from Gene Expression Ominus (GEO), including GSE39582 test series(N=436), internal validation series (N=117); and two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
127
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(129 citation statements)
references
References 40 publications
2
127
0
Order By: Relevance
“…The expression profiles of lncR-NA have been characterized in many diseases by microarray and RNA-seq. recently, researchers have demonstrated that annotation of published microarray data is a feasible and reliable method to profile lncRNA expression [27,28]. In the current study, we re-annotate the HG U133Plus2.0 microarrays and analyzed lncRNA expression profile of lymphatic endothelial cells in diabetic and non-diabetic patients.…”
Section: Discussionmentioning
confidence: 97%
“…The expression profiles of lncR-NA have been characterized in many diseases by microarray and RNA-seq. recently, researchers have demonstrated that annotation of published microarray data is a feasible and reliable method to profile lncRNA expression [27,28]. In the current study, we re-annotate the HG U133Plus2.0 microarrays and analyzed lncRNA expression profile of lymphatic endothelial cells in diabetic and non-diabetic patients.…”
Section: Discussionmentioning
confidence: 97%
“…LncRNAs are frequently found to be aberrantly expressed in cancers, yet only a few studies developed lncRNA-based prognosis signature [29,30]. In this study, we constructed the prognosis signature for predicting CRC DFS based on the resulting risk score of every sample, whose lncRNA profiling data was obtained from previous published studies.…”
Section: Discussionmentioning
confidence: 99%
“…The same results were observed in an independent testing dataset GSE57317. Similar approaches on improving prognosis prediction using lncRNA have been studied in many cancers; [38][39][40][41][42] however, few in MM. Top 20 out of 176 lncRNAs were most significantly expressed associated with survival of MM patients.…”
Section: Discussionmentioning
confidence: 99%